2018
DOI: 10.1186/s12891-018-2322-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between liver enzymes and bone mineral density in Koreans: a cross-sectional study

Abstract: BackgroundOsteoporosis is a major health concern for both men and women, and associated fractures incur substantial economic burden. While there are a multitude of studies on bone mineral density (BMD) and liver diseases, not many studies have assessed the association between liver enzyme levels and BMD in homogeneous populations.MethodsThe current study investigated the association between serum liver enzyme levels and BMD at various sites in Koreans. Out of 21,517 surveyees of the 5th Korean National Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 59 publications
2
9
1
1
Order By: Relevance
“…Previous studies have shown that OP is a common skeletal complication in patients with chronic liver disease, [ 20 , 21 ] and a cross-sectional study in Korea shows that there is a negative correlation between liver enzyme level and BMD, and there is a significant correlation between OP/BMD reduction and liver disease. [ 22 ] This is inconsistent with our results and may require further study (Table 5 ).…”
Section: Resultscontrasting
confidence: 98%
“…Previous studies have shown that OP is a common skeletal complication in patients with chronic liver disease, [ 20 , 21 ] and a cross-sectional study in Korea shows that there is a negative correlation between liver enzyme level and BMD, and there is a significant correlation between OP/BMD reduction and liver disease. [ 22 ] This is inconsistent with our results and may require further study (Table 5 ).…”
Section: Resultscontrasting
confidence: 98%
“…In previous studies, increased blood GGT level has been associated with osteoporosis and decreased BMD. (3,10) These results support the possibility that GGT is involved in bone metabolism and may be associated with osteoporosis and related fractures. Moreover, variability in metabolic parameters, including GGT, is closely related to inflammation-associated metabolism and dysregulation of homeostasis, which may be associated with cardiovascular diseases and osteoporosis.…”
Section: Introductionsupporting
confidence: 71%
“…Recently, it has been reported that GGT level is also associated with other diseases including cardiovascular disease and osteoporosis and decreased bone mineral density (BMD) and with mortality as well. (13) To confirm the association between a specific biomarker and disease risk, it may be more reliable to determine whether variability in multiple measurements is more highly associated with risk than is change in only one measurement. In this context, GGT variability is closely related to risk of myocardial infarction, stroke, and heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, being in the highest tertile of serum GGT level increased the risk of low bone mass, leading to osteopenia and osteoporosis. Another investigation including 7160 Koreans also demonstrated that GGT had a relatively clear negative association with BMD at multiple sites 25 . A study regarding the association between liver markers and short-term outcomes in patients with hip fracture demonstrated that higher GGT levels at the time of admission increased the risk of a prolonged hospital stay 26 .…”
Section: Discussionmentioning
confidence: 94%